Answer:

y = 3/4x

Remember

Rise/Run

From one point, to another.

**Answer:**

444

**Step-by-step explanation:**

28*5

17*5

17*3

56*3

add the answers

**Answer:**

(x - 1)(x - 3)(x + 2).

**Step-by-step explanation:**

f(1) = 1^3 - 2(1)^2 - 5(1) + 6

= 1 - 2 - 5 + 6

= 0

so one factor is **(x - 1) **(by the Factor Theorem).

Divide f(x) by x - 1 we get:

x- 1) x^3 - 2x^2 - 5x + 6 ( x^2 - x - 6 <------ answer

x^3 - x^2

-x^2 - 5x

-x^2 + x

-6x + 6

-6x + 6

= x^2 - x - 6

=** (x - 3)(x + 2).**

15/12=10/x

x=0.125. Hope it help!